Influence of supplementation thre17-28 e type of Phytogenic plants in diet on growth Performance, intestinal microflora and immunity of Broiler Cobb-500. - Mahmmod, Zhian A.; Abdulrazaq, Hurea Saber; Sadiq, Rubar Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2017)
This study was conducted to evaluate the effects of three herbal medical plants, Chamomile flowers (Matericariachamomilla L), Black cumin seeds (Nigella sativa L) and Thyme (Thymus vulgaris) on growth performance, carcass characteristics, immune system, and intestinal bacterial populations in broiler Cobb-500. A total of two hundred forty (240) Cobb500, one-day old broiler chicks were randomly divided to four experimental groups (60) chicks/treatment, which divided to (3) replicates (20 Chicks / replicate). The dietary treatments were: (T1) basal diet as control, (T2) basal diet plus 1kg of Chamomile flowers(Matericariachamomilla L) to 100kg diet, (T3) basal diet plus 1kg Black cumin seeds(Nigella sativa L) to 100 kg diet, .(T4) basal diet plus 1kg of the Thyme (Thymus vulgaris) to 100 kg diet. The experiment was lasted for (42) days. Live body weight (LBW), Weight Gain (WG), Feed Intake (FI), Feed Conversion Ratio (FCR) were measured at the end of feeding program ( 21, 35 and 42 days) of age. At the end of the experiment carcass characteristics, immunological properties such as antibody titer against Newcastle disease virus as well as relative weight of bursa fabricia, spleen and total mortality rate were measured. The groups fed (T2) Chamomile flowers (Matericariachamomilla L) and (T3) Black cumin seeds (Nigella sativa) showed significantly (p>0.05) higher value for Live body weight (LBW) as compared with (T1, T4) groups. No significant differences were observed in feed conversion ratio (FCR) and total Feed intake (FI) at period (1-42 days). Results showed that total Mortality decreased significantly (p<0.05) in all treatment compared with those birds fed control group (T1). The results showed that relative weights of lymphoid organs (spleen, bursa fabrecius) as an indicator of the immune system condition was significant (P<0.05) high weight of spleen observed at all treatments with supplementation of dietary herbs compared with control group (T1)..Antibody responses to Newcastle Disease were improved significantly (p<0.05) antibody levels increased by treatments (T3, T4). The result shows that treatments (T3, T4) were lead to significantly (p<0.05) decreased of total counts of coliform bacterial in jejunum compared with (T1, T2) groups.
Keywords: Medical plants; Growth performance; Immunity; Mortality; and Micro flora